2017
DOI: 10.1186/s12882-017-0517-6
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported non-adherence and immunosuppressant trough levels are associated with rejection after renal transplantation

Abstract: BackgroundDifferent measures of non-adherence to immunosuppressant (IS) medication have been found to be associated with rejection episodes after successful transplantation. The aim of the current study was to investigate whether graft rejection after renal transplantation is associated with patient-reported IS medication non-adherence and IS trough level variables (IS trough level variability and percentage of sub-therapeutic IS trough levels).MethodsPatient-reported non-adherence, IS trough level variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
2
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 36 publications
4
55
2
5
Order By: Relevance
“…Overall the present study showed that nonadherence was because of suboptimal implementation of the IS medications the first post‐transplant year. Self‐reported nonadherence using BAASIS © in this population was 29% at 1‐year, which is in line with previous studies . As other reports also have shown , the majority of these NoAd patients took all the prescribed doses but had a time deviation (22%).…”
Section: Discussionmentioning
confidence: 99%
“…Overall the present study showed that nonadherence was because of suboptimal implementation of the IS medications the first post‐transplant year. Self‐reported nonadherence using BAASIS © in this population was 29% at 1‐year, which is in line with previous studies . As other reports also have shown , the majority of these NoAd patients took all the prescribed doses but had a time deviation (22%).…”
Section: Discussionmentioning
confidence: 99%
“…Reinforced action by a systematic review of self-reported instruments to identify noncompliance with medication, where BAASIS® was recommended as a reliable, valid and sensitive tool. (21) Measurement of adherence has implications for nursing and interdisciplinary practice, and it is relevant because of the high investment of the public health system-more than 50% of the annual transplantation budget is directed to immunosuppressant drugs. (22) Therefore, the evaluation of adherence in recipients who have undergone transplantation must be considered to support actions for the therapeutic plan after KTP and in this way will help reduce investment in treatment of complications due to nonadherence.…”
Section: Discussionmentioning
confidence: 99%
“…Die Non-Adhärenz-Schwelle wird also sehr niedrig angelegt. Dennoch muss bei einer Selbsteinschätzung immer von einer Erinnerungsverzerrung ("recall bias") ausgegangen werden, sowie dem Wunsch des Patienten, sozial erwünschtes Verhalten zu zeigen [19]. Dies kann zur Folge haben, dass non-adhärente Verhaltensweisen nicht berichtet werden und es dadurch zu einer Unterschätzung der Non-Adhärenz kommt [14,19,20].…”
Section: Selbsteinschätzungunclassified
“…Allerdings ist nicht jede Spiegelveränderung auf Unregelmäßigkeiten in der Medikamenteneinnahme zurückzuführen. Auch durch pharmakokinetische Phänomene und Interaktionen zwischen verschiedenen Medikamenten können Veränderungen des Immunsuppressiva-Spiegels hervorgerufen werden [19,22]. Schäfer-Keller et al [20] kommen zu dem Schluss, dass eine Adhärenzbestimmung auf Grundlage der Spiegel zu einer Überschätzung der Non-Adhärenz führt.…”
Section: Bestimmung Der Medikamentenspiegelunclassified
See 1 more Smart Citation